Position statement for a pragmatic approach to immunotherapeutics in patients with inflammatory skin diseases during the coronavirus disease 2019 pandemic and beyond - Beecker J; Papp KA; Dutz J; Vender RB; Gniadecki R; Cooper C; Gisondi P; Gooderham M; Hong CH; Kirchhof MG; Lynde CW; Maari C; et al. (Wiley, 2021)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, a novel RNA virus that was declared a global pandemic on 11 March 2020. The efficiency of infection with SARS-CoV-2 is reflected by its rapid global spread. The SARS-CoV-2 pandemic has implications for patients with inflammatory skin diseases on systemic immunotherapy who may be at increased risk of infection or more severe infection. This position paper is a focused examination of current evidence considering the mechanisms of action of immunotherapeutic drugs in relation to immune response to SARS-CoV-2. We aim to provide practical guidance for dermatologists managing patients with inflammatory skin conditions on systemic therapies during the current pandemic and beyond. Considering the limited and rapidly evolving evidence, mechanisms of action of therapies, and current knowledge of SARS-CoV-2 infection, we propose that systemic immunotherapy can be continued, with special considerations for at risk patients or those presenting with symptoms.
Keywords: COVID-19; Dermatitis; Humans; Immunotherapy; Practice Patterns, Physicians'; Risk Assessment